Pelatihan Pembuatan Video Pembelajaran Online Bagi Guru PAUD di Kecamatan Parigi Kabupaten Parigi Moutong - Nurhayati Nurhayati; Amrullah Amrullah; Durrotunnisa Durrotunnisa; Sita Awalunisah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This community service aims to provide training to PAUD teachers in Parigi District, Parigi Moutong Regency in the form of providing knowledge so that teachers can understand making online learning videos. The subjects in this study were 16 teachers at Aisyiyah Dolago Kindergarten, Parigi Moutong Regency. The method used is in the form of training and education, namely by using pretest and posttest, lectures, discussions, ice breaker, energizer and games. Furthermore, the data is processed using SPPSS 16.0 for windows, namely the gain score and inferential test. The results of the service show that there is a positive and significant influence of technical training on teachers' understanding of teachers' understanding of making online learning videos. This is shown by Sig < α (0.016 < 0.05) meaning that the gain score of the teacher's understanding of making online learning videos before training is significantly different from after training. In addition, it can be seen from the results of the average pretest score in the teacher group, namely 64.6, while in the posttest, the average score increased to 96.7. In the teacher group, the highest score in the pretest was 85, while in the posttest the highest score increased to 115. Furthermore, the lowest score in the teacher group in the pretest was 39 and in the posttest it increased to 79. In the teacher group, the standard deviation value in the pretest was 13.84 and in the posttest that is 11.1. Based on the description above, it can be concluded that training is effective for teacher understanding regarding making learning videos for PAUD teachers in Parigi District, Parigi Moutong Regency.